PEMBERDAYAAN MASYARAKAT DALAM MEWUJUDKAN DESA JATIREJO SEBAGAI DESA WISATA EDUKASI - Aryaningtyas, Aurilia Triani; Suwarti, Suwarti; Prabowo, Bayu Ade; Putriningsih, Tiara Sanika L.; Laia, Flores H. (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2024)
This community service initiative aims to unlock the maximum potential of Jatirejo Village as an educational tourism destination through comprehensive community empowerment. The main challenges include low awareness of local tourism, lack of guiding skills, and lack of expertise in creating attractive educational tour packages. A multifaceted approach was applied to address this issue. Activities carried out include tourism awareness outreach, tour guide training, and training in preparing attractive tourism packages. Total of 54 partners were involved in this activity, consisting of tourism village administrators and the community. The impact of this program is expected to be very large, namely increasing public awareness, improving driving skills, and developing attractive educational tour packages. It is hoped that the results of this activity can contribute to improving the welfare of local communities and the progress of the local tourism sector more broadly. The success of this activity will create a conducive environment for economic growth and encourage sustainable development in Jatirejo Village as a growing educational tourism destination.